Gender Awareness and Donor Participation: Transforming Zakat Distribution for Enhanced Community Welfare - Zayid Yıldırım, Mehmed; El-Din Fatma, Aisha (Journal International Economic Sharia, 2025)
Objective: Institutional mechanisms and stakeholder participation play pivotal roles in providing welfare effects in social finance distribution systems.Methods: We use survey data and a hierarchical regression to test direct as well as moderating effects.Results: Welfare outcomes are greatly improved when institutional transparency, gender-sensitive practices, and professional management are ensured. We identify stakeholder participation, in particular, as an important moderating factor, which indeed serves to significantly bolster the association between institutional practices and the realization of welfare gains. The combined model explains better that integrating operational excellence with active involvement creates a synergistic impact.Novelty: This paper brings in the catalyzing role of stakeholder participation as a moderator and proposes a convergent theoretical framework by integrating four arguably understudied institutional perspectives, such as marketing and service, which offers rare insights in the social finance literature on effectiveness.Research Implication: This study fills this gap and opens new avenues for research by providing a potential basis for designing more effective social welfare programs and furthering theoretical development through the validation of an integrated model of institutional effectiveness.